Great Patriotic War in Soviet and Post-Soviet Cinematography: Problems of Remediation - K. V. Igaeva; F. V. Nikolai (Научный диалог)
The article is devoted to the representations of the Great Patriotic War in Soviet and postSoviet cinematography. The study presents the comparative analysis of the heroic narrative dating back to wartime propaganda and most clearly manifested in post-war film epics, as well as the tragic narrative, which is inextricably linked with the ‘lieutenant’ prose of the Thaw-era. The changes in the images of the Soviet cinema in the Russian war films of the 2000s are considered. It is proved that these changes, found in modern series and remakes, are critically evaluated by both academic circles and youth audience. On the basis of discussions held in ten focus groups the main critical attitudes are analyzed. Particular attention is paid to the problem of remediation which consists in the predominance of visual images only outwardly copying popular Soviet films, without independent reflection on the specificity and the meaning of military experience. It is noted that the concept of remediation makes it possible to shift the focus from dissatisfaction with individual parts of films about the Great Patriotic War to the general problem of changing the media regime in modern society and to start analyzing the mechanisms of its functioning.